1997
DOI: 10.1136/bmj.315.7099.18
|View full text |Cite
|
Sign up to set email alerts
|

Substance use in remand prisoners: a consecutive case study

Abstract: Objective: To investigate the association of dietary pattern and mortality in international data. Design: Cohort study with 20 years' follow up of mortality. Setting: Five cohorts in Finland, the Netherlands, and Italy. Subjects: Population based random sample of 3045 men aged 50-70 years in 1970. Main outcome measures: Food intake was estimated using a cross check dietary history. In this dietary survey method, the usual food consumption pattern in the 6-12 months is estimated. A healthy diet indicator was ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
2
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 10 publications
3
53
2
1
Order By: Relevance
“…Women's prisons had the lowest rate of selfreported use (15 episodes per 100 inmates per week). (Mason et al, 1997) reported that 57 per cent had used illicit drugs in the year prior to coming to prison and 33 per cent met DSM-IV criteria for drug misuse or dependence. The 1997 ONS survey of prisoners in England and Wales (Singleton et al, 1998) found a prevalence of reported drug use in the year preceding the current term of 55 per cent of female sentenced prisoners, 66 per cent of female remand and male sentenced prisoners and 73er cent of male remand prisoners.…”
Section: Key Findingsmentioning
confidence: 99%
“…Women's prisons had the lowest rate of selfreported use (15 episodes per 100 inmates per week). (Mason et al, 1997) reported that 57 per cent had used illicit drugs in the year prior to coming to prison and 33 per cent met DSM-IV criteria for drug misuse or dependence. The 1997 ONS survey of prisoners in England and Wales (Singleton et al, 1998) found a prevalence of reported drug use in the year preceding the current term of 55 per cent of female sentenced prisoners, 66 per cent of female remand and male sentenced prisoners and 73er cent of male remand prisoners.…”
Section: Key Findingsmentioning
confidence: 99%
“…60 Those addicted to opiates and those who inject drugs are over-represented in the prison population 61,62 and research indicates that a high proportion of prisoners are dependent on tobacco and alcohol. 12,57,63,64 In addition to individual health behaviours, multifaceted social issues face the prison population, which in turn impact on health. 14,65 Many of those entering the criminal justice system have experienced a lifetime of social exclusion, including a poor educational background, low income, meagre employment opportunities, lack of engagement with normal societal structures, low self-esteem and impermanence in terms of accommodation (including bouts of homelessness) and relationships with family members.…”
Section: Determinants Of Offender Healthmentioning
confidence: 99%
“…Data regarding the prevalence of stimulant drug use in prisons are limited and it is therefore problematic to view this as representative of the actual situation as previous research has shown that the numbers are by definition an understatement (Knight et al, 1998;Mason et al, 1997). However, studies have highlighted some important issues for consideration such as the different type of drug use prevalent in prisons, and the various factors which explain this.…”
Section: Introductionmentioning
confidence: 99%
“…Stimulant use has been identified as more prevalent in pre-trial prisons, or within pre-trial sections of prisons compared to sentenced prisons (especially on drug-free wings) which is attributed to the presence of more dealers and the absence of urine testing (Mason et al, 1997;Brooke et al, 1998). However, studies have also shown that prisoners usually prefer depressant-type drugs in prison as these can be used more readily to produce relaxation and to relieve boredom (Swann & James, 1998;Bullock, 2003;Strang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation